Peningkatan Kualitas Perkecambahan Biji Cendana (Santalum album Linn.) dengan Lama Perendaman Menggunakan Air Kelapa dan Bawang Merah - Tinia Blegur; Mamie E. Pellondo’u; Wilhemina Seran (Wana Lestari, 2023)
Sandalwood (Santalum album Linn.) is an endemic plant that is the identity of the people of East Nusa Tenggara (NTT). Generative propagation by means of seed soaking treatment is one of the alternatives to sandalwood plant propagation. Factors that are known to affect the success of plant propagation are Growth Regulators (ZPT) and the duration of soaking. This study was conducted to determine the use of coconut water and shallots as well as the effect of soaking duration for sandalwood growth. The research method uses a Complete Randomized Design (RAL) using a factorial design of 2 (two) factors, namely the first factor in the use of coconut water and shallots consisting of 3 levels, namely aquades (control), air kelapa 75% and bawang merah 75% and The second factor includes the length of soaking which consists of 3 levels, namely the Soaking Time of 9 Hours, 18 Hours, and 27 Hours. The results of this study showed that the treatment of the use of Coconut Water and Shallots and the combination of treatments did not have a real effect on germination, germination speed index, germination value and wet weight, while the length of soaking had a significant effect on the germination power and has avery noticeable influence on the sandalwood germinating speed index (Santalum album LINN).